“It Should Have Been Given Sooner, and We Should Not Have to Fight for It”: A Mixed-Methods Study of the Experience of Diagnosis and Early Management of Cerebral Palsy - Williams, Sian; Alzaher, W.; Mackey, A.; Hogan, A.; Battin, M.; Sorhage, A.; Stott, N.S. (MDPI, 2021)
Listening to the family experience is integral to identifying areas of strength and for im-provement in health service delivery around diagnosis and early management of cerebral palsy (CP). Families of children with a diagnosis of CP were invited to complete a purpose-developed electronic survey that included items around the timing of diagnosis, their experiences and satisfaction. It also allowed families to expand on their experiences through free text. Of the 57 families responding, 49% of children functioned at Gross Motor Function Classification System (GMFCS) levels I or II, 8% at GMFCS level III and 23% at GMFCS levels IV or V. 51% of participants were satisfied or very satisfied with the diagnosis experience, 18% were neutral about the experience and 31% were dissatisfied or very dissatisfied. Though the findings of this study may be subject to selection bias, perceived delays in the receipt of diagnosis of CP appeared common with 60% of participants indicating concerns about their child by <6 months of age but only 21% provided with a diagnosis of CP <6 months of age. Approximately 18% of families experienced a delay of more than 12 months. Thirty-four (61%) participants noted a delay between referrals to a service and receipt of service management/therapy. Common themes impacting on families’ experience in the diagnosis and health service delivery journey related to provision of information, and the style of communication, with both direct and ongoing communication styles common for greater family satisfaction. Overall, families desired the diagnosis experience to be informative and timely, with early follow up support and assistance with health sector navigation.